Evolution of clinical features in possible DLB depending on FP-CIT SPECT result. (6th September 2016) - Walker, Zuzana; Moreno, Emilio; Thomas, Alan; Inglis, Fraser; Tabet, Naji; Stevens, Tim; Whitfield, Tim; Aarsland, Dag; Rainer, Michael; Padovani, Alessandro
Abstract : Objective: To test the hypothesis that core and suggestive features in possible dementia with Lewy bodies (DLB) would vary in their ability to predict an abnormal dopamine transporter scan and therefore a follow-up diagnosis of probable DLB. A further objective was to assess the evolution of core and suggestive features in patients with possible DLB over time depending on the 123 I-FP-CIT SPECT scan result. Methods: A total of 187 patients with possible DLB (dementia plus one core or one suggestive feature) were randomized to have dopamine transporter imaging or to follow-up without scan. DLB features were compared at baseline and at 6-month follow-up according to imaging results and follow-up diagnosis. Results: For the whole cohort, the baseline frequency of parkinsonism was 30%, fluctuations 29%, visual hallucinations 24%, and REM sleep behavior disorder 17%. Clinician-rated presence of parkinsonism at baseline was significantly ( p = 0.001) more frequent and Unified Parkinson's Disease Rating Scale (UPDRS) score at baseline was significantly higher ( p = 0.02) in patients with abnormal imaging. There was a significant increase in UPDRS score in the abnormal scan group over time ( p < 0.01). There was relatively little evolution of the rest of the DLB features regardless of the imaging result. Conclusions: In patients with possible DLB, apart from UPDRS score, there was no difference in the evolution of DLB clinical features over 6 months between cases with normal and abnormal imaging. Only parkinsonism and dopamine transporter imaging helped to differentiate DLB from non-DLB dementia.